Greater volumes of static and dynamic stretching within a warm-up do not impair star excursion balance performance - Belkhiria-Turki, L.; Chaouachi, A.; Turki, O.; Hammami, R.; Chtara, M.; Amri, M.; Drinkwater, E. J.; Behm, D. G. (The Journal of Sports Medicine and Physical Fitness, 2014)
Based on the conflicting static stretching (SS) literature and lack of dynamic stretching (DS) literature regarding the effects of differing volumes of stretching on balance, the present study investigated the effects of 4, 8, and 12 sets of SS and DS following a 5 min aerobic running warm-up on the star excursion balance test (SEBT). The objective was to examine an optimal stretch modality and volume to enhance dynamic balance. A randomized, within-subjects experimental design with repeated measures for stretching (SS and DS) versus no-stretching treatment was used to examine the acute effects of 10 (4 sets), 20 (8 sets), and 30 (12 sets) min, of 15s repetitions per muscle of SS and/or DS following a 5 min aerobic warm-up on the performance of the SEBT. Results indicated that a warm-up employing either SS or DS of any volume generally improves SEBT by a "small" amount with effect sizes ranging from 0.06 to 0.50 (11 of 18 conditions>75% likely to exceed the 1.3-1.9% smallest worthwhile change). Secondly, the difference between static and dynamic warm-up on this observed improvement with warm-up improvement was "trivial" to "moderate" (d=0.04 to 0.57) and generally "unclear" (only two of nine conditions>75% likely to exceed the smallest worthwhile change). Finally, the effect of increasing the volume of warm-up on the observed improvement with a warm-up is "trivial" to "small" (d<0.40) and generally "unclear" (only three of 12 conditions>75% likely to exceed the smallest worthwhile change). In summary, an aerobic running warm-up with stretching that increases core and muscle temperature whether it involves SS or DS may be expected to provide small improvements in the SEBT.